Self-Powered Electrical Bandage Based on Body-Coupled Energy Harvesting - Kang, Minki; Yum, Han-Yup; Kim, Hyoung Taek; Park, Byung-Joon; Cho, Daniel Sanghyun; Choi, Younghwan; Kim, Hye Jin; Cho, Youngmin; Kim, Young-Jun; Lee, Dong-Min; Lee, Dong-Gyu; Song, Hyun-Cheol; et al. (WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim, 2024)
Self-powered electrical bandages (SEBs), integrated with wearable energy harvesters, can provide an effective and autonomous electrical stimulation (ES) solution for rapid and scarless wound healing. A continuously operating, wireless, and applicable-to-comprehensive-wound ES device is essential for the quick restoration of wounds and convenience. This work illustrates a SEB powered by body-coupled energy harvesting. The SEB continuously treats the wound with 60-Hz sinusoidal electrical potential gained from the coupling of the human body and ambient electrical waves. It is demonstrated that enough level of electrical potential can be applied to the wound, further enhanced by strong capacitive coupling arising from the use of high-permittivity poly(vinylidene fluoride-trifluoroethylene):CaCu3Ti4O12 (P(VDF-TrFE):CCTO) nanocomposite. The potential clinical efficacy of the SEB is illustrated by preclinical analysis of human fibroblasts and mouse wound model, thus confirming the successful expedition of wound recovery. This work suggests a new class of wearable devices to provide ES events and its potential for extension to other conventional wound care materials and device technology. An innovative SEB based on high-permittivity P(VDF-TrFE) nanocomposites is designed to provide autonomous and effective electrical treatment that accelerates wound healing by leveraging body-coupled energy harvesting from ambient 60-Hz EM waves. Combining human-centered energy solution and flexible, skin-conformable design, this work suggests the potential of the SEB as a straightforward, convenient, and practical wound care apparatus. image